Combustion synthesis and characterization of Mg-based Fe-doped biphasic calcium phosphate ceramics - Kaygili, Omer (Springer Heidelberg, 2019)
Mg-based (0.35 at.%) biphasic calcium phosphates (BCPs) doped with Fe at various amounts (e.g., 0.35, 0.70 and 1.05 at.%) were prepared by the combustion method. The X-ray diffraction (XRD) analysis confirmed the biphasic structure, composed of hydroxyapatite (HAp) and beta-tricalcium phosphate (-TCP) for each sample. While -TCP content increases, HAp content decreases with increasing Fe levels. The crystallinity decreased with the addition of Fe. The unit cell parameters and crystallite size were affected by Fe content. The existence of both phosphate and hydroxyl groups in the samples was verified by the Fourier transform infrared (FTIR). A mass gain was observed for each BCP. The formation of the rod-shaped particles was observed.
Keywords: In-Vitro; Biocompatibility; Bioceramics; Porosity